The Difficulties in Indonesian-English Translation on the Sixth Semester of the English Education Study Program of Muhammadiyah Kotabumi University: A Case Study - Rulik, Rulik Setiani; Dewi Sri Kuning (Universitas Cokroaminoto Palopo, 2023)
Translation is a skill in the process of replacing a message or written statement from one language with a message and statement of the same in another language, where the message and statement conveyed from the source language must be the same as the target language. In fact there are several aspects of difficulties that make students’ difficulties in translation. Those aspects are lexical, grammatical, and stylistic difficulties. The objectives of this research are (1) to describe the difficulties in translating Indonesian-English on the sixth semester students of English education study program of Muhammadiyah Kotabumi University, and (2) to find out the difficulties dominate in translating Indonesian-English on the sixth semester students of English education study program of Muhammadiyah Kotabumi University. The method will be used is qualitative case study method. The researchers will use sampling techniques to get the information and data which is needed by the researchers. Purposive sampling is a sampling technique with certain considerations. In this case the researchers take 6 students who got low score of translating Indonesian-English as subject of the research. The research data is obtained from documents which this case are the results of students’ Indonesian-English translation. The researchers will use the data analysis model of Miles and Huberman. Activities in this data analysis will use data reduction, data presentation, and drawing conclusions/verification. From the data analysis shows that